Appraisal of the Factors that Hinders Effective Implementation of Universal Basic Education Policy in Public Junior Secondary Schools in Adamawa State - Muhammad Saratu Mera (EDUJAVARE: International Journal of Educational Research, 2023)
The paper examined the factors that hinder the effective implementation of the Universal Basic Education Policy in Adamawa State, Nigeria. Four research questions and four research objectives guided the study. Descriptive research design was adopted for the study. The population of the study consisted of 254 junior secondary schools, 4500 teachers, and 254 principals in Adamawa state. The sample of the study was drawn using deliberate and stratified random sampling techniques, while a proportionate sampling technique was used to determine the sample size required from each school. Data for the study was obtained using a questionnaire. The instrument was validated by measurement, evaluation, and education management experts in the Department of Educational Foundations, Usmanu Danfodiyo University Sokoto. A pilot test was conducted using Cronbach Alpha, and a reliability index of 0.79 was realized. Data collected was analyzed using frequency counts, percentage, mean, and standard deviation, while an independent T-test was used to test the hypothesis generated. Findings from the study indicated that: insufficient funding, poor planning, and inadequate professionally qualified teachers are some of the challenges that mar the successful implementation of the UBE program in Adamawa state. The study recommended, among others, that the government should make efforts to counter the factors which have become impediments to the successful implementation of the UBE program, such as the provision of adequate funding, qualified professional teachers, and instructional materials.